The Concept of Qibla Direction in Sayyid Usman’s Tahrir Aqwa Al-Adillah Fi Tahsil ‘Ain Al-Qiblah - nanaridwan, Mau'idhatul Hasanah Ridwan; Ahmad Izzuddin; Fatmawati Hilal (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
Establishing the correct Qibla direction is essential for Muslims when performing prayers, particularly in distant regions like Southeast Asia, far from the Kaaba. This study examines the viewpoints and techniques of Sayyid Usman bin Abdullah bin Aqil bin Yahya in ascertaining the Qibla, as documented in his manuscript Tahrir Aqwa al-Adillah fi Tahsil ‘Ain al-Qiblah, while evaluating its significance within the framework of Islamic astronomy and historical context. A qualitative methodology was adopted, relying on textual analysis of the primary source alongside supplementary scholarly references. The research highlights Sayyid Usman’s integrative approach, blending religious principles with astronomical calculations to ensure precision in Qibla alignment. His techniques included observing rasd al-qiblah the phenomenon where the sun aligns vertically above the Kakbah and tracking the position of the star Arcturus (as-Simak) for regions like Java and the Malay Peninsula. His work differentiates between the exact bearing of the Kaaba (‘ain al-qiblah) and its approximate direction (jihah al-qiblah), advocating for expertise in astronomical science (‘ilm al-falak) to issue accurate religious rulings. Furthermore, he challenged unsubstantiated practices, urging adherence to rigorous scholarly interpretation (ijtihad) or the guidance of qualified jurists. In conclusion, Sayyid Usman’s contributions in Tahrir Aqwa al-Adillah fi Tahsil ‘Ain al-Qiblah advanced both theoretical and practical dimensions of Qibla determination in the Malay Archipelago. His methodologies transcended their era, retaining applicability in contemporary settings and offering potential synergy with modern advancements. This work exemplifies how interdisciplinary harmony between Islamic jurisprudence and empirical science can yield actionable solutions to theological challenges.